Effect of Intradermal Tumor Necrosis Factor-α-induced Inflammation on Coagulation Factors in Dermal Vessel Endothelium - Speiser, Wolfgang; Kapiotis, Stylianos; Kopp, Christoph W.; Simonitsch, Ingrid; Jilma, Bernd; Jansen, Burkhard; Exner, Markus; Chott, Andreas (Thrombosis and Haemostasis, 2001)
Inflammatory mediators were shown to exert procoagulant effects on cultured human endothelial cells (EC). In the present study the effect of intradermal application of tumor necrosis factor- (TNF-) on the expression of factors involved in regulation of coagulation at the EC surface, i. e. tissue factor (TF), thrombomodulin (TM) and tissue factor pathway inhibitor (TFPI) was studied in humans in vivo. The endothelial expression of these factors was evaluated immunohistochemically in biopsies taken after intradermal application of 5000 U TNF- in 8 healthy volunteers. After 6 and 22 h biopsies were taken from the injection sites. At TNF- injected sites typical inflammatory changes, e. g. EC upregulation of adhesion molecules and accumulation of leukocytes were detected. In parallel we could document EC expression of TF, downregulation of TM and depletion of tissue factor pathway inhibitor (TFPI) in inflamed areas. Early depletion of endothelial I B at the site of inflammation after application of TNF- points to an activation of the NF- B pathway. Our data suggest that, as shown in in vitro experiments, TNF- activates the NF- B pathway and induces specific procoagulant changes of EC due to expression of TF, down-regulation of TM and depletion of TFPI in vivo in humans. This procoagulant shift in the haemostatic balance on the cell surface, caused by TNF- -induced inflammation, is likely to contribute to thrombosis associated with tissue inflammation in humans.
Keywords: TNF-α; human endothelial cell; tissue factor